Broadband terahertz spectroscopy of amino acids. Issue 4 (4th July 2017) - Yi, Wenting; Yu, Jiangping; Xu, Yutian; Wang, Fang; Yu, Qi; Sun, Haijun; Xu, Li; Liu, Yunfei; Jiang, Ling
ABSTRACT: Broadband spectra of 20L -amino acids were obtained at room temperature by terahertz time-domain and infrared spectroscopy. The intensity of terahertz absorption peaks varied with the concentrations of amino acids, and the optimum proportion for each amino acid was obtained. An absorption spectral database of 20L -amino acids was established from 0 to 6 THz. The associations between terahertz absorption peaks and molecular structures of amino acids were analyzed. The terahertz spectra forL -alanine were compared with the calculated results based on density functional theory using two basis sets that were reliably consistent.